Anatomy collections as "modern ruins": The nostalgia of lonely specimens. Issue 2 (June 2021) - Ion, Alexandra
Argument: This text is a reflection on the fate of a special kind of scientific object - anatomy collections - and their place in contemporary times. Though the phenomenon of keeping and displaying such collections is generally dying out, those specimens which survive continue to puzzle and fascinate us. To understand the current status of such collections, and the nostalgia evoked by the specimens within them, I argue, we should approach them as modern ruins. This allows us to think of them as places of absence, pointing to unfinished lives and unfinished scientific projects. The paper begins with the story of a preserved human face from the Francis I. Rainer anatomical-anthropological collection (Bucharest), and continues by discussing the fate of that collection, and of anatomy collections more widely. Ultimately, the paper asks, what is it that we want to preserve: specimens, practices, or research philosophies?